Play, History and Politics: Conceiving Futures Beyond Empire - Fordyce, Robbie (Games and Culture, 2021)
The worlds of games are important places for us to think about time, as demonstrated by historical game studies in evaluating the past, but there is a role for games to help us consider the future as well. Because games are, to some extent, systems, they facilitate a systems thinking approach that connects the material to the immaterial. Because games also tend to be action-based, they allow thinking through of acts as well as representations. Games allow us to think about a time and place that is different from the present and how it might operate as a system that we could live in. I argue that a post-autonomist method of game analysis requires an explicitly political interpretation that is focused on trying to imagine a political future through experiments in gaming.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing at Being Mobile: Gaming and Cute Culture in South Korea - Hjorth, Larissa (Fibreculture Journal, 2006)
This paper is based on ongoing research into the gendered use of mobile convergent media in the Asia-Pacific region. In particular, what role does the cute have and how does it correlate with types of consumption? As a region, the Asia-Pacific is marked by diverse penetration rates, subject to local cultural and socio-economic nuances. Two defining locations - Seoul (South Korea) and Tokyo (Japan) - are seen as both mobile centres and gaming centres which the world looks towards as examples of the future-in-the-present. Unlike Japan, which pioneered the keitai (mobile) IT revolution with devices such as i-mode, South Korea has become a centre for mobile DMB (Digital Multimedia Broadband) with the successful implementation of TV mobile phones (TU mobile) in 2005. One of the key features of mobile media technologies is the attempt by the industry to find the next killer application . One such application is the possibility of online multiplayer games accessed through mobile (broadband) telephonic devices such as MMO golf RPG Shot Online (a golf game for mobile phones). Amongst this frenzy of trend spotting and stargazing, Seoul as a mobile broadband and gaming centre provides a curious case study for the social and cultural intricacies informing the rise of gaming as an everyday practice for many Koreans.This article begins by outlining the game play and technoculture particular to South Korea and then explores the phenomenon of Kart Rider in South Korean gaming cultures - and its perception/ reception outside Korea - to sketch some of the issues at stake in playing it cute (particularly in the form of cute avatars), consuming Korea and the endurance of co-present communities. In particular, it contemplates the implications of current emerging online mobile gaming genres such as so-called female games such as the cute' Kart Rider in order to think about changing modes of game play and attendant social spaces.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé